2010
DOI: 10.1038/npp.2010.17
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Altered Polyamine Concentrations in Cerebral Cortex of Suicide Completers

Abstract: Recent studies have implicated alterations in the expression of polyamine-related genes in the brains of suicide completers including widespread downregulation of spermidine/spermine N1-acetyltransferase, the key enzyme in polyamine catabolism, suggesting compensatory mechanisms attempting to increase brain levels of polyamines. Given the complexity of the polyamine system, quantification of the levels of the polyamines is an essential step in understanding the downstream effects of dysregulated gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 68 publications
2
36
0
Order By: Relevance
“…This increased histone methylation was associated with decreased expression; however differences in DNA methylation were only seen in the frontal cortex (BA10) and not the cerebellum. Additionally, in line with the study on peripheral BDNF levels in antidepressant drug responders [57] previously described, a study using suicide brains found that antidepressants use had the same association of decrease in methylation at H3K27 and an increase in BDNF expression [71], again suggesting an influence of therapeutic drugs on histone modifications in humans similar to that seen in rodents [72].…”
Section: Chronological Agesupporting
confidence: 60%
“…This increased histone methylation was associated with decreased expression; however differences in DNA methylation were only seen in the frontal cortex (BA10) and not the cerebellum. Additionally, in line with the study on peripheral BDNF levels in antidepressant drug responders [57] previously described, a study using suicide brains found that antidepressants use had the same association of decrease in methylation at H3K27 and an increase in BDNF expression [71], again suggesting an influence of therapeutic drugs on histone modifications in humans similar to that seen in rodents [72].…”
Section: Chronological Agesupporting
confidence: 60%
“…This technique was specifically developed for the extraction and quantification of spermine, spermidine, putrescine, and agmatine from postmortem brain [57,58,59]. Using GC-MS, it was shown that putrescine and spermidine levels were significantly elevated in the brains of depressed suicide completers [60], thus lending further support to the idea that decreases in SAT1 expression in depressed suicide completers are likely the result of a feedback regulation.…”
Section: -Protein Levels Of Polyaminesmentioning
confidence: 89%
“…The PSR, like the HPA axis, is implicated in physiological responses to physical, emotional and hormonal stressors, including glucocorticoids (BOX 4). The mRNA and protein levels of several components of the polyamine system are altered in cortical and subcortical brain regions of suicide completers [125][126][127][128] , as well as in peripheral samples from suicide attempters 129,130 and psychiatric patients 131 .…”
Section: Trait Markersmentioning
confidence: 99%